Heterolepic β‐Ketoiminate Zinc Phenoxide Complexes as Efficient Catalysts for the Ring Opening Polymerization of Lactide. Issue 7 (4th July 2019) - Ghosh, Swarup; Schäfer, Pascal M.; Dittrich, Dennis; Scheiper, Christoph; Steiniger, Phillip; Fink, Gerhard; Ksiazkiewicz, Agnieszka N.; Tjaberings, Alexander; Wölper, Christoph; Gröschel, André H.; Pich, Andrij; Herres‐Pawlis, Sonja; et al.
Abstract: Zinc phenoxide complexes L 1 ZnOAr 1 –4 (L 1 =Me2 NC2 H4 NC(Me)CHC(Me)O) and L 2 ZnOAr 5 –8 (L 2 =Me2 NC3 H6 NC(Me)CHC(Me)O) with donor‐functionalized β ‐ketoiminate ligands (L 1/2 ) and OAr substituents (Ar=Ph 1, 5 ; 2, 6‐Me2 ‐C6 H3 2, 6 ; 3, 5‐Me2 ‐C6 H3 3, 7 ; 4‐Bu‐C6 H4 4, 8 ) with tuneable electronic and steric properties were synthesized and characterized. 1 –8 adopt binuclear structures in the solid state except for 5, while they are monomeric in CDCl3 solution. 1 –8 are active catalysts for the ring opening polymerization (ROP) of lactide (LA) in CH2 Cl2 at ambient temperature and the catalytic activity is controlled by the electronic and steric properties of the OAr substituent, yielding polymers with high average molecular weight ( M n ) and moderately controlled molecular weight distribution (MWDs). 1 and 5 showed a living polymerization character and kinetic studies on the ROP of L –LA with 1 and 5 proved first order dependencies on the monomer concentration. Homonuclear decoupled 1 H‐NMR analyses of polylactic acid (PLA) formed with rac ‐LA proved isotactic enrichment of the PLA microstructure. Abstract : Zinc it through : The syntheses and structures of a series of heteroleptic β ‐ketiminate zinc phenoxide complexes is reported. These species are highly active catalysts for the ring‐opening polimerization of lactide in CH2 Cl2 at ambient temperature.